Cultivating Knowledge about Canadian Women Scientists through Seminars, Objects, and Exhibitions - Stelmackowich, Cindy (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2019)
Exhibtion research and development can be an innovative way to cultivate new knowledge in university classrooms. This article describes a Carleton University seminar that incorporated collections-based research to study Canadian women scientists. Entitled “Representations of Women’s Scientific Contributions,” the seminar gave students the opportunity to apply feminist critiques to the material cultures of science as they wrote the cultural histories of scientific objects related to the women they studied. The seminar culiminated in HERbarium, a well-receieved exhibition at the Carleton Univeristy Art Gallery in 2017.